The Use of Music to Connect the Past, Present, and Future. Issue 5 (3rd September 2022) - Ender, Tommy; Varga, Bretton A.
Abstract: Artists have long addressed social injustices within popular music. As teachers consider how to deconstruct and teach the events of 2020 (and beyond) with an eye toward the future, we offer a novel pedagogical approach to incorporating music into the social studies classroom: the set-list. The set-list can be understood as containing temporal conditions insofar that all traditional demarcations of time (e.g., past, present, and future) are implicated in its construction. Extending the concept of the set-list into education holds excellent potential for teachers and students seeking to develop a more complex perspective about criticality and social in/justice. Our set-list example originates from years-long conversations around our experiences as former secondary social studies teachers, current teacher educators, fathers, spouses, and individuals living in the United States. Music encourages students to recognize how the past, present, and future are intertwined in learning history. While the official social studies curriculum does not include music as an approach to learning history in the social studies classroom, using a student-generated set-list starts transforming the world within the context of social justice.